(untitled) (Development Service Industry Management, 2023)
The increasing competition among restaurant businesses necessitates the search for new approaches to maintaining market stability. In this context, the study explores the interrelationship between innovative potential, service quality, operational efficiency, and competitive advantages of restaurant enterprises. The article aims to develop theoretical and practical foundations for managing the competitive development of restaurant businesses by identifying key directions for managerial influence. A structural equation modeling (PLS-SEM) approach was employed to design and empirically validate a model of competitive advantage formation. The theoretical framework of this model is based on the resource-based view of competitive advantage, the concept of innovation-driven service sector development, service management theory, and the principles of operational excellence. The study’s core hypothesis posits that the sustainable competitive development of restaurant enterprises is driven by continuous innovation. Within this framework, competitive advantage management is proposed to be structured around the design and commercialization of innovations. The structural equation model empirically tests hypotheses regarding the alignment of key theoretical elements. The modeling environment utilized was the ADANCO software package. The study is based on survey data collected from internal stakeholders, industry experts, and restaurant customers, employing specifically developed evaluation criteria and a Likert scale. The path coefficient analysis highlights the pivotal role of innovative potential as both a direct and indirect driver of competitive advantage in the restaurant industry. The study’s findings offer valuable insights for determining investment priorities to enhance the competitive positioning of restaurant enterprises, optimizing resource allocation across different business dimensions, and formulating a balanced innovation strategy that ensures competitive sustainability without compromising market stability.